Of Scrapes and Scratches: A Preliminary Study on the Use-wear of Porcelain Sherds from Structure A, Pinagbayanan, San Juan, Batangas, Philippines - Kintanar, Andrea Natasha E. (Hukay, 2014)
Research conducted by the University of the Philippines-Archaeological Studies Program in San Juan, Batangas began with a survey in 2008. This led to a systematic archaeological excavation of a stone house in Barangay Pinagbayanan, San Juan, Batangas in 2009. Subsequent excavations were conducted from 2010 in the same stone house, in 2011 of a second stone house and in 2012 of the old church ruins. Use-wear or use-alteration analysis was performed on the porcelain sherds recovered from the 2010 excavation. Specifically, scratches and abrasions probably left by utensils were identified and examined. Porcelains recovered from the site were Chinese, European, and some American white ware. Since ceramics also have non-utilitarian purposes, some preliminary assumptions are offered as to whether these sherds were from a utilitarian or decorative piece. Use-wear analysis helps in inferring activity patterns within and between different areas of a site (Griffiths 1978). In the Philippines, this is the first use-wear experiment done on porcelain sherds from a historical site. The results show that the specimens investigated were possibly porcelains used for both decorative and dining purposes.